ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA BADAN KELUARGA BERENCANA, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN KUTAI KARTANEGARA - Winarti, .; S. Riadi, Sukisno; Ulfah, Yana (Jurnal Ekonomi Pembangunan, 2013)
The purpose of this study was to analyze the effect of variable motivation, leadership and organizational culture on the performance of an employee of the Agency for Family Planning, Women's Empowerment and Child Protection Kutai regency in Tenggarong and variables that have a dominant influence on employee performance. The conclusion of this research tends to count the resulting F value of 40.495 with a probability level of 0.000. While the value of F table is 2.736 indicating that the F count> F table and significance of 0.000 <0.05, which means that the variable motivation, leadership and organizational culture together have a significant effect on employee performance.